HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERILAKU PENCEGAHAN INFEKSI LEPTOSPIROSIS PADA IBU HAMIL - Intan Nugraheni Hasanah; Sri Wahyuni (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2017)
Leptospirosis is spread all over the world, on all continents, except the Antarctic continent. Most incidents are found in tropical countries, including Indonesia. According to the International Leptospirosis Society, Indonesia is a country with a high incidence of leptospirosis, and ranks third in the world for mortality.This study aims to determine the relationship of knowledge and attitude with the prevention behavior of leptospirosis infection in pregnant women. The type of research is explanatory research using cross sectional approach method. Subjects were all pregnant women who were not suffering from leptospirosis infection in Bandarharjo Semarang Public Health Center. Sampling technique using Total Sampling. Univariate analysis of each variable with percentage size. Bivariate analysis using Chi Square statistic.The result of this research got the knowledge level of pregnant woman to behavior of prevention of leptospirosis infection in Bandarharjo Semarang Public Health Center mostly belong to good category (70,6%). The attitude of pregnant mother to behavior of prevention of leptospirosis infection in Bandarharjo Semarang Public Health Center mostly belong to positive category (58%). There is correlation between knowledge and attitude with behavior of prevention of leptospirosis infection in pregnant woman in Bandarharjo Semarang Public Health Center area.This research is expected to motivate people to be more active in finding information about leptospirosis or other health problems.